OVARIAN ACID PHOSPHATASES FROM RANA CYNOPHLYCTIS (SCHN.) - BHOSALE, SUNITA M.; PATIL, SUBHASH; KANASE, ARUNA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1994)
Ovaries of Rana cynophylyctis (Schn.) in prebreeding condition were studied for acid phosphatase (AcPase) activities. The results obtained from biochemical characterization indicated that there were three species of enzymes acting at different pH. AcPase I (3.7 pH), AcPase II (4.4 pH) and AcPase III (5 pH). AcPase I was Mg*", Mn* ", Cut", citrate and glycerol dependent enzyme. AcPase II was Mg" and Mn'" activated and sensitive to Ca' and citrate. AcPase III was Mn** and Cu** activated and sensitive to Ca**, and citrate. AcPase I, AcPase II and AcPase III were theremal activated and sensitive to methanol, ethanol, acetone, triton X-100, formaldehyde and sodium fluoride.